Manajemen Likuiditas Lembaga Keuangan Mikro Syariah Non Bank (BMT) dengan Akad Tawarruq - Edi Susilo (Jurnal Ilmiah Ekonomi Islam, 2017)
Non-bank Islamic microfinance institutions (BMT) are legal entity Cooperative have no instrument to fulfill liquidity needs as Islamic banking. Whereas the BMT should provide liquidity fund for the partners / members at any time. This article uses descriptive analytical method, to understand deeply the Tawarruq contract as liquidity management solutions Non-bank Islamic Microfinance Institutions  (BMT). The results show the Tawarruq contract can be revitalized by necessity of the present to fulfill the liquidity needs of Non-bank Islamic Microfinance Institutions (BMT). Keywords: Tawarruq, Islamic Microfinance Institutions, BMT